Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di Puskesmas Pampang Makassar - Sapang, Rianty; Zainal , Syaifuddin; Arna Abrar, Eva (STIKES Nani Hasanuddin, 2025)
Hypertension is a degenerative disease that is often found in society and occurs frequently. The aim of this study was to determine the effect of deep breathing relaxation techniques on reducing blood pressure in hypertensive patients at the Pampang Community Health Center. This research uses an experimental design with this type of research design being Pretest-Posttest observation. The technique used was providing instructions and exercises regarding deep breathing realization techniques to the intervention group and the control group as a comparison. The number of respondents was 30 people consisting of 15 respondents in each group, the intervention group was given deep breathing relaxation techniques and the control group was given no treatment. The results of the paired samples t-test in the intervention group, the difference between pretest and posttest systolic blood pressure was 2,000 mmHg, with a value of P=0.01 (P<0.05) and diastolic blood pressure, the difference between pretest and posttest was 1,600 mmHg, with a value of P=0.01 (P <0.05). Meanwhile, in the control group, the difference between systolic blood pressure and pretest and posttest was 0.133 mmHg, with a P value = <0.001 (P>0.05) and diastolic blood pressure, the difference between pretest and posttest was 0.4667 mmHg, with a P value = 0.192 (P>0.05). It can be concluded that the deep breathing relaxation technique has been proven to have a significant effect on reducing systolic and diastolic blood pressure in hypertensive patients.